2019
DOI: 10.1002/jcp.28681
|View full text |Cite
|
Sign up to set email alerts
|

Condensin II subunit NCAPH2 associates with shelterin protein TRF1 and is required for telomere stability

Abstract: Condensin II subunits are known to be expressed and localized to interphase nuclei of eukaryotic cells. Although some studies have shown that condensin II likely exerts axial compaction forces, organizes chromosome territories, and has possible transcriptional modulatory functions, the full range of condensin II interphase activities are not known. In particular, it is not known if condensin II interphase activities are generally genome‐wide or if they have additional local activities unique to specific chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 65 publications
4
23
1
Order By: Relevance
“…Our data indicate that cells with ≥4 γH2AX foci are not enriched in S‐phase (Figure 5a,b), and that knockdown of CAPH2 or expression of R551P mutant CAPH2 causes G1 arrest/delay (Figure 5c–g). RNAi depletion of CAPH2 causes RPA recruitment to telomeres (Wallace et al, 2019), indicating a role for condensin II in preventing ssDNA formation at telomeres. It is possible that ssDNA present at telomeres leads to sister chromatid telomere fusions observed after depletion of CAPH2 (Wallace et al, 2019), and that these fusions cause chromosome breakages during mitosis that are inherited as damaged DNA in G1 of the next cell cycle (Giunta et al, 2010; Lezaja & Altmeyer, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that cells with ≥4 γH2AX foci are not enriched in S‐phase (Figure 5a,b), and that knockdown of CAPH2 or expression of R551P mutant CAPH2 causes G1 arrest/delay (Figure 5c–g). RNAi depletion of CAPH2 causes RPA recruitment to telomeres (Wallace et al, 2019), indicating a role for condensin II in preventing ssDNA formation at telomeres. It is possible that ssDNA present at telomeres leads to sister chromatid telomere fusions observed after depletion of CAPH2 (Wallace et al, 2019), and that these fusions cause chromosome breakages during mitosis that are inherited as damaged DNA in G1 of the next cell cycle (Giunta et al, 2010; Lezaja & Altmeyer, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the actions of condensin I and II in vivo could also be further modulated and regulated by co-factors present in the cellular environment. There is an ever-increasing list of condensin I or II specific co-factors including but not limited to, the chromo kinesin KIF4A, telomere-associated TRF1 and TANK1, cell cycle factors RB1, pRB and Plk1, chromatin modeller component, Arid1a, the transcription factor, TFIIIC and DNA damage response factor, MCPH1 [78][79][80][81][82][83][84][85][86][87]. The role of condensin I and II binding partners in the structural organisation of the genome is largely unknown.…”
Section: Holocomplex Structurementioning
confidence: 99%
“…ARID1A plays an important role at the enhancer regions. ChIP-seq experiments using ovarian cancer cell-lines demonstrated that more than 80% of the peaks are localized at the enhancers and promoters, and that ARID1A co-localizes with a subunit of the condensin complex II called NCAPH2, which has recently been shown to associate with the shelterin protein, TRF1, and regulate telomeric stability ( Wallace et al, 2019 ). ARID1A knockout affected the binding of NCAPH2 at H3K27Ac-marked enhancers genome-wide.…”
Section: Remodeling Activities Required For Higher Order Chromatin Stmentioning
confidence: 99%